Muli-Quay Combined Berth and Quay Crane Allocation Using the Cuckoo Search Algorithm - Aslam, Sheraz; Michaelides, Michalis P.; Herodotou, Herodotos (My University, 2024)
This study investigates the combined berth allocation problem (BAP) and quay crane allocation problem (QCAP) while considering a multi-quay setting. First, a mixed integer linear programming mathematical model is developed based on various constraints and real port settings. Then, the multi-quay combined BAP and QCAP is solved using both the exact method and a metaheuristic optimization method, namely, the cuckoo search algorithm (CSA). This analysis pertains to a one-week planning scenario, utilizing data from a real port. The results of the comparative analysis show that the proposed CSA can provide a near-optimal solution (< 1.02% from the optimal) at a fraction of the computational time (10 times faster), as compared to the exact solution. This makes it suitable for solving larger instances of the combined BAP and QCAP for bigger terminals and extended planning horizons.
Keywords: Berth and Quay Crane Allocation Problem; Cuckoo Search Algorithm; Metaheuristic; Port Efficiency